2021
DOI: 10.1016/j.ajog.2021.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcomes of pregnant women with SARS-CoV-2 infection at the time of birth in England: national cohort study

Abstract: BACKGROUND: Some studies have suggested that women with SARS-CoV-2 infection during pregnancy are at increased risk of adverse pregnancy and neonatal outcomes, but these associations are still not clear. OBJECTIVE: This study aimed to determine the association between SARS-CoV-2 infection at the time of birth and maternal and perinatal outcomes. STUDY DESIGN: This is a population-based cohort study in England. The inclusion criteria were women with a recorded singleton birth between May 29, 2020, and January 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
214
5
22

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(253 citation statements)
references
References 34 publications
12
214
5
22
Order By: Relevance
“…In relation to preeclampsia, no significant differences in the incidence among patients with severe and non-severe COVID-19 have been observed; this finding is contradictory to previous studies in which higher rates of preeclampsia have been demonstrated in cases of severe COVID-19 [32][33][34].…”
Section: Comparison With Existing Literaturecontrasting
confidence: 93%
“…In relation to preeclampsia, no significant differences in the incidence among patients with severe and non-severe COVID-19 have been observed; this finding is contradictory to previous studies in which higher rates of preeclampsia have been demonstrated in cases of severe COVID-19 [32][33][34].…”
Section: Comparison With Existing Literaturecontrasting
confidence: 93%
“…In large cohort studies, the overall risk of severe neonatal outcomes as well as neonatal infection related to maternal SARS‐CoV‐2 infection seems low, however, a recent paper reports increased rates of fetal death, preterm birth, preeclampsia, emergency cesarean delivery, and other adverse maternal and neonatal outcomes. 33 High‐quality evidence syntheses of comparative studies as well as studies describing detailed clinical observations from cases with adverse outcomes are needed to guide future clinical decisions in pregnancies complicated by COVID‐19. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding perinatal outcomes following SARS-CoV-2 infection, several reports of miscarriage and stillbirth were published [49,50], as well as pathological findings such as placentitis [51] and placenta thrombosis [52]. Premature births have been shown to be more common in SARS-CoV-2-positive mothers and their newborns are more likely to be admitted to the neonatal care unit [45].…”
Section: Epidemiology Of Sars-cov-2 Infectionmentioning
confidence: 99%